Integration of LabVIEW for novel interactive learning courseware on digital electronics - Yap, Wing Fen; Mohd Sabri, Luqman Al-Hakim (International Educative Research Foundation and Publisher, 2014)
Digital electronics involves communication between systems or instruments in digital form. Digital electronics is an important field in physics and engineering, and included in the syllabus in almost all higher learning institutions. The main objective of this study is to develop an interactive learning courseware for Digital Electronics with the integration of LabVIEW applications in order to facilitate the learning process of Digital Electronics. The novel developed courseware mainly covers the basics of digital electronics. The integration of LabVIEW enables students to get hands on real time experiences as in a real laboratory. These virtual laboratories can be accessible anytime and anywhere. Students can interact with the courseware which makes the learning process more dynamic.